Evolution of carving motifs in malay vernacular architecture in Kelantan and Terengganu - Nursuriani Shaffee; Ismail Said (2010)
Consistency of floral motifs on Malay woodcarving is unmistakable considered as essential component in traditional Malay vernacular architecture in Kelantan and Terengganu, north-eastern region of Peninsular Malaysia since after 14th Century. This paper presents an exploratory study on the evolution of floral motif in Malay woodcarving in the period of establishment 1850s to present. It examines visual descriptive and interpretative analysis of 32 carved components on mosques, palaces, traditional houses and resort in Kelantan and Terengganu as data of carving motif which obtained from measured drawings from the Centre for the Study of Built Environment in the Malay World at Universiti Teknologi Malaysia. Drawings of 32 carved component were analyzed using point pattern analysis and quadrant count method to find the changes of flora motif. The result suggests that the evolution of floral motifs have changed gradually as the complexity of floral motif consists of abstract leaves and branches integrated in pleasant composition. The factors of the changes are possibly influenced by the type of buildings, carving values toward plant materials of the era, the behaviors of Malay culture, and the significance of placement carved components in the buildings.